The effect of estrogen on muscle damage biomarkers following prolonged aerobic exercise in eumenorrheic women - T Williams; E Walz; AR Lane; M Pebole; AC Hackney (Termedia Publishing House, 2015)
This study assessed the influence of estrogen (E 2 ) on muscle damage biomarkers [skeletal muscle - creatine kinase (CK); cardiac muscle - CK-MB] responses to prolonged aerobic exercise. Eumenorrheic women (n=10) who were physically active completed two 60-minute treadmill running sessions at ~60-65% maximal intensity during low E 2 (midfollicular menstrual phase) and high E 2 (midluteal menstrual phase) hormonal conditions. Blood samples were collected prior to exercise (following supine rest), immediately post-, 30 min post-, and 24 hours post-exercise to determine changes in muscle biomarkers. Resting blood samples confirmed appropriate E 2 hormonal levels Total CK concentrations increased following exercise and at 24 hours post-exercise were higher in the midfollicular low E 2 phase (p<0.001). However, CK-MB concentrations were unaffected by E 2 level or exercise (p=0.442) resulting in the ratio of CK-MB to total CK being consistently low in subject responses (i.e., indicative of skeletal muscle damage). Elevated E 2 levels reduce the CK responses of skeletal muscle, but had no effect on CK-MB responses following prolonged aerobic exercise. These findings support earlier work showing elevated E 2 is protective of skeletal muscle from exercise-induced damage associated with prolonged aerobic exercise.